Naturalising a heavily modified urban river: Initial habitat evolution in the Manzanares River (Madrid, Spain). (3rd January 2022) - Díaz‐Redondo, María; Marchamalo, Miguel; Morcillo, Felipe; King, James J.
Abstract: Between the 1910s and 1960s, the segment of the Manzanares River in the city of Madrid was channelized to allow for intensive urban development and a series of barrages were built to maintain constant water levels and create the aesthetic of a large deep river. As part of a renaturalisation strategy for the river by the Madrid City Council, the complete opening of the barrages' hydraulic gates in spring 2016 allowed for natural physical processes to occur that, in turn, facilitated colonisation of newly‐formed habitats by vegetation and fauna. The present study evaluates the initial effects of the barrage gate openings on instream habitats through the analysis of (i) geomorphological, physico‐chemical and vegetation metrics, and (ii) hydraulic variables associated with potential preferential conditions for native fish fauna, whose populations were greatly diminished. This approach incorporates an integrative view of the multivariate nature of the fluvial ecosystem. Results show a substantial reactivation of habitat heterogeneity over a short timeframe. In addition, newly‐emerging habitat conditions, related to sediment activation, improved water quality and diversified hydraulic conditions, are promoting potential preferential habitats for native fish fauna. This study can help aquatic researchers and administrators in understanding how an urban river can evolve with a cost‐effective intervention focused on the recovery of self‐forming dynamics. This application of process‐based river restoration strategies to a heavily modified river can also lead to the improvement of its ecological potential, as required by the European Union's Water Framework Directive.